2017
DOI: 10.1016/j.oregeorev.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of mineralizing fluids and exploration of the Cerro Quema Au-Cu deposit (Azuero Peninsula, Panama) from a fluid inclusion and stable isotope perspective

Abstract: Cerro Quema is a high sulfidation epithermal Au-Cu deposit with a measured, indicated and inferred resource of 35.98 Mt. @ 0.77 g/t Au containing 893,600 oz. Au (including 183,930 oz. Au equiv. of Cu ore). It is characterized by a large hydrothermal alteration zone which is interpreted to represent the lithocap of a porphyry system. The innermost zone of the lithocap is constituted by vuggy quartz with advanced argillic alteration locally developed on its margin, enclosed by a well-developed zone of argillic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The lack of hydrogen isotope values, as well as lack of knowledge of the isotopic composition of meteoric fluids in THMB at the time of mineralization, prevents definitive identification of fluid sources (e.g., Mehrabi et al, 2016). Studies of fluid-mineral isotopic equilibrium in geothermal systems have shown that quartz is very resistant to isotopic exchange and preserves its original isotopic signature (Clayton et al, 1968;Taylor, 1968;Blattner, 1975;Clayton and Steiner, 1975;Fifarek and Rye, 2005;Corral et al, 2017). If the hydrothermal fluids had uniform oxygen isotopic composition, the increase in δ 18 O would reflect decreasing temperatures of mineral precipitation, which is in agreement with the decrease in the homogenization temperatures obtained from fluid inclusions.…”
Section: Ore-forming Fluids and Sulfur Sourcessupporting
confidence: 55%
See 1 more Smart Citation
“…The lack of hydrogen isotope values, as well as lack of knowledge of the isotopic composition of meteoric fluids in THMB at the time of mineralization, prevents definitive identification of fluid sources (e.g., Mehrabi et al, 2016). Studies of fluid-mineral isotopic equilibrium in geothermal systems have shown that quartz is very resistant to isotopic exchange and preserves its original isotopic signature (Clayton et al, 1968;Taylor, 1968;Blattner, 1975;Clayton and Steiner, 1975;Fifarek and Rye, 2005;Corral et al, 2017). If the hydrothermal fluids had uniform oxygen isotopic composition, the increase in δ 18 O would reflect decreasing temperatures of mineral precipitation, which is in agreement with the decrease in the homogenization temperatures obtained from fluid inclusions.…”
Section: Ore-forming Fluids and Sulfur Sourcessupporting
confidence: 55%
“…Cooling, mixing, boiling and water-rock reaction are the main factors that can promote the precipitation of precious and base metals from an ore fluid in the epithermal environment (e.g., Giggenbach and Stewart, 1982;Heald et al, 1987;Hayba, 1997;Hedenquist et al, 2000;Federico et al, 2002;Zhai et al, 2009;Corral et al, 2017). Boiling is considered to be the main factor leading to deposition of precious metals in many epithermal deposits (e.g., Izawa et al, 1990;Simon et al, 1999;Faure et al, 2002;John et al, 2003), whereas the dilution and/or cooling resulting from fluid mixing are key mechanisms for base metal precipitation (e.g., Spycher and Reed, 1989;Yilmaz et al, 2007Yilmaz et al, , 2010Kouhestani et al, 2015Kouhestani et al, , 2017.…”
Section: Mineralization Model and Genetic Typementioning
confidence: 99%
“…Hydrothermal alteration at Cerro Quema follows an eastward trend that is parallel to secondary faults related to the Río Joaquín Fault Zone. It is defined by several concentric alteration halos that are mainly restricted to dacite domes of the Río Quema Formation, which have higher porosity and permeability than other rock types of the volcano-sedimentary sequence (Corral et al, 2017). According to Corral et al (2011Corral et al ( , 2016, four distinct alteration zones can be identified at Cerro Quema: several vuggy quartz centers (up to ~600 m in length) and local advanced argillic alteration zones (up to ~250 m in length) are observed within the central core of the deposit, enclosed by an argillic alteration zone (up to ~1900 m in length).…”
Section: Hydrothermal Alterationmentioning
confidence: 99%
“…The propylitic alteration zone contains chlorite, epidote, calcite, rutile, pyrite, chalcopyrite, and minor hematite and mag-netite. Stable isotope (S, O, H) geochemistry and fluid inclusion studies revealed that hydrothermal alteration at Cerro Quema was produced by magmatic-hydrothermal fluids that were variably mixed with meteoric fluids (Corral et al, 2017).…”
Section: Hydrothermal Alterationmentioning
confidence: 99%
See 1 more Smart Citation